(De)Legitimizing Violence: Gendering the Arab Spring - A Comparative Analysis of Institutions in Egypt and Tunisia - ElMorally, Reham (Richtmann Publishing, 2020)
The Arab Spring (2011) was characterized by uprisings in various Arab countries that attempted to oust their respective regimes. The revolutions diffused from the movement in Tunisia to the rest of the Arab countries. The Arab Spring was followed by what is now commonly known as the Arab Winter, i.e. the resurgence of the authoritarian and oppressive regimes and array of radicalization. This research attempts to compare and contrast the uprisings in Egypt, which is considered a failed story, and Tunisia, which is considered a success story. The underlying question is: what are the institutional and social structures that exist in the respective countries that have amounted to their success/failure? The hypothesis is that Tunisia’s social and institutional configurations are more gender conscious than Egypt’s, leading to a stronger and more resilient superstructure that encapsulated the aggregate of the population instead of lobbying for the interests of the social hegemonic blocs. In other words, Tunisia’s society might be more aware of the bargaining power the historically marginalized women have in ousting the regime, as opposed to the Egyptian population. This awareness is reflected in the structure of political institutions, the power dynamics within those institutions, and affects the selection and orientation of decision-makers.